The old man by the sea - Starnone, Domenico, 1943- (Europa Editions, 2025)
"Domenico Starnone's The Old Man by the Sea is a slim masterpieceof a novel about an 82-year-old Neapolitan man, Nicola, who has spent his entire life telling stories, becoming very, very good at it. In words, with his pen, in the notebook he carries with him everywhere, he records life's minutiae, its ephemera, those vibrating essences and almost imperceptible atoms of existence that most of us barely notice but that constitute the very stuff of life. Yes, recording the universe in each grain of sand has become second nature to Nicola. But of course, there is always something that escapes. Something unnamable that resists, remaining on the margins, slithering away, amovement intuited rather than identified. And this fact, for Nicola, is a source of deep anxiety and a growing sense of failure. Now, ensconced in a house on the dunes south of Rome, Nicola spends his mornings writing, watching the waves, and observing Lu, a store clerkin her twenties whose graceful canoeing stirs faint echoes of his mother--a glamorous, headstrong woman who defied convention with her beauty and creativity. As Nicola reflects on the women who shaped him and the passions he has never outgrown, he finds himself drawn into the nefarious intrigues of the small seaside town and its inhabitants. He will end by embarking on an improbable and ill-advised kayak adventure of his own with Lu's young son, as Starnone himself brings this slim, virtuoso novel about eros and melancholy, memory and reinvention, age and imagination, to an unexpected conclusion"--